Policy and regulatory frameworks for agritourism development in India: A scoping review - Komal Jenifer Dsouza; Ankitha Shetty; Pooja Damodar; Jeet Dogra; Nachiket Gudi (Cogent Social Sciences, 2024)
Among the many verticals in India’s rich kaleidoscope of tourism services, agritourism offers a vivid rural experience to tourists. National and state-level tourism policies focused on agritourism play a pivotal role in its performance enhancement. Despite its potential, the country needs a foundational framework through a National Tourism Policy. This missing link encouraged us to conduct a scoping review to synthesize and understand policy interventions in India aimed at promoting agritourism by following the guidelines espoused by Arksey and O’Malley. Individual policies of India’s states and union territories were synthesized to understand the significance of agritourism in the region. We also searched for scientific articles on Scopus, Web of Science and Google Scholar that focused on agritourism development through policy dimensions and regulatory frameworks. The results are presented through the lens of Carol Bacchi's framework. In the final review, 23 documents were included. Our findings reflect an urgent need to develop and implement policies that define strategic and financial support to encourage farmers to take up agritourism on their land. In addition, the development of agritourism policies must be followed by implementation and monitoring through definitive institutional mechanisms.